Satellite mission to study the Van Allen belts - Drishana Jhunjhunwalla; Debani Prasad Mishra; Jayanta Kumar Sahu; Dashmat Hembram; Surender Reddy Salkuti (Institute of Advanced Engineering and Science, 2023)
The Van Allen belts are said to be a pack of highly energetic particles which are extremely fatal to electronic systems and living beings. Very little information is known about them. Besides the data from past missions, it’s still not enough to draw any conclusion regarding the phenomenon of its shape, size, and density. The paper talks of a cost-effective satellite mission named Vansat to study the Van Allen belts in depth. The project aims to study the energetic particles, magnetic fields, and plasma waves in the radiation belts. The mission also focuses on having environment-friendly concepts demonstrated through the technologies along with a reduction in the complexity of the devices and instruments. Vansat consists of a dual satellite system-one satellite to study the inner belt and the other to study the outer belts. The octagonal geometry of the satellite along with wings and solar panels ensure aero dynamicity, energy saving as well as radiation shielding.